The Application of ChatGPT-based AI Technology in the Field of Campus Psychological Counseling - Liu, Che; Zhang, Jiajia; Wang, Mengmeng (Transactions on Social Science, Education and Humanities Research, 2023)
The emergence and popularization of generative AI technology represented by ChatGPT mark the transformation from weak AI to strong AI, and bring opportunities and challenges to education. In recent years, mental health issues have gradually become a social problem faced by countries around the world, including China. These mental health issues have gradually expanded from adults and professional groups to students, and are showing a trend of "low age". Strengthening the mental health education of adolescents has become a consensus of the whole society. However, there are currently a lack of excellent counselors in primary and secondary schools, or the number of counselors is relatively small, resulting in a large amount of tasks. In order to study how ChatGPT can help school counselors provide better services, first analyze the basic principles and characteristics of ChatGPT technology. Then discuss the application practice of ChatGPT in psychological counseling, including as an auxiliary tool for counselors, a self-help psychological therapy platform, and a mental health education tool, combined with campus scenarios. Finally, explore the possible challenges and limitations of ChatGPT technology in the application of campus psychological counseling, and propose future research directions.